(untitled) (Nonconventional Technologies Review, 2019)
The electrical discharge machining could be used sometimes to improve the roughness of the machined surfaces. The values of the surface roughness parameters are affected by the characteristics of the electrical discharges developed between the closest asperities existing on the active surface of the tool electrode and on the workpiece surface to be machined. An electrical discharge machining scheme based on the use of tubular tool electrodes was applied to detach cylindrical parts from a parallelepipedal workpiece. An experimental research was developed to highlight the influence exerted by the pulse on time, pulse off time and average peak current intensity on some of the surface roughness parameters which take into consideration the amplitude of the asperities corresponding to the machined surface, in the case of a test piece made of high speed steel HS18-1-1-0. Power type mathematical empirical models were determined by mathematical processing of the experimental results and using a specialized software. The analysis of the empirical mathematical models showed that the values of the surface roughness parameters increase when the average peak current intensity increases and slowly decrease when the values of the pulse on time increase also. In our case, one noticed that for the experimental conditions, the pulse off time practically does not affect the values of the considered surface roughness parameters.